(untitled) (Research, Society and Development, 2022)
Emergency contraception is an oral method arranged to prevent unwanted pregnancy soon after unprotected intercourse, and it should be used for emergency only. Due to its free access, irrational use, and lack of guidance, many women are prone to develop a thromboembolism because of inappropriate use. Pulmonary embolism (PE) is characterized by the occlusion of a pulmonar vessel or artery caused by a thrombus, an air embolism or a fat clot, that has developed in the body. There are risk factors that contribute to the development of embolism, such as: hormonal contraception, adiposity, being immobile for long periods of time, age group, arterial fibrillation, and smoking and type 2 diabetes mellitus. The purpose of this study is to analyze literature review articles that relate the development of thromboembolism coupled with the use of emergency contraception. This is an integrative bibliographic review study, carried out through a survey in the VHL and GOOGLE ACADEMIC, with the crossing of descriptors pulmonary thromboembolism AND contraception. It has been evidenced that there is an association between the development of thrombus with the use of contraception, whether it is the combined oral pill, or the emergency pill. We conclude that to reduce the risks of thromboembolism associated with the use of emergency contraception, medical evaluation is necessary to assess the need and adherence of each patient.